Vegetation stands structure and aboveground biomass after the shifting cultivation practices of Karo People in Leuser Ecosystem, North Sumatra - T. ALIEF ATHTHORICK; DEDE SETIADI; YOHANES PURWANTO; EDI GUHARDJA (Society for Indonesian Biodiversity, 2012)
Aththorick TA, Setiadi D, Purwanto Y, Guhardja E. 2012. Vegetation stands structure and aboveground biomass after the shifting cultivation practices of Karo People in Leuser Ecosystem, North Sumatra. Biodiversitas 13: 92-97. Vegetation stands structure and aboveground biomass after the shifting cultivation practices of Karo People in Leuser Ecosystem, North Sumatra. Shifting cultivation has been practiced by Karo People in Leuser Ecosystem for a very long time and caused a mosaic of patches that shift over time between traditional agriculture and secondary forest. The objectives of this study were to investigate the recovery of vegetation stands structure and aboveground biomass in four age classes of secondary forest, i.e. 5-years old, 10-years old, 20-years old, 30-years old andprimary forest as a control. In total, 496 subplots were surveyed. Saplings contributed 62.82% of basal area in 5-years forest and still important in 10 and 20-years forest, but density decreased in 30-years and primer forest whereas tree stands dominated in 30-years and primary forest and shared basal area of 96.36% and 97.03%, respectively. Aboveground biomass of trees achieved its highest values in primary forest, i.e. 659.22 t/ha and contributed to total aboveground biomass of 99.38%.